Hegel e o sentido do político. Uma investigação sobre a possibilidade de uma Aufhebung do trabalho - Barros, Douglas Rodrigues [UNIFESP] (2020)
The term politics which has a very old tradition in philosophy is especially linked to the very emergence of philosophy. The displacement of the individual, the break with his accommodation given by the coup of reason established a kind of logical revolt that culminated in the idea of a fair Republic. The destitution of the sacred and the logical and inscrutable character of the concrete facts of nature and human life will be basic assumptions of Hegel's thought. However, far from a notion guided by reason itself without interfering in reality, Hegel brings to the historical ground, for the experience of the unfolding of the spirit, the formation of the sense of the political. Thinking about the stripping of political meaning in its relation to the unfolding of the category of work, our hypotheses aim to think about politics from the category of experience and its relationship with the advent of the work of the spirit in Hegel's Phenomenology of Spirit.